The envy-contempt spiral: affective self-regulation in grandiose narcissism - Raftopoulos, Alexandros; Unterrainer, Human-Friedrich (Frontiers in Psychiatry, 2025)
In classic psychoanalytic theory, narcissism and envy have been theorized to be inseparably interwoven. Nevertheless, empirical findings have not yet been able to substantiate this relationship. Conversely, most studies showed that grandiose facets of narcissism curbed feelings of envy, suggesting an envy-protection inherent to grandiose narcissism. Consistent with these findings, contemporary psychodynamic accounts, specifically object-relations theory, conceptualize grandiose narcissism as a defensive structure against envy via the elicitation of contempt. In the present paper, we translate this theory to contemporary personality psychology by drawing on Affective Neuroscience and socio-functional approaches of emotion. We propose that envy and contempt interact in a self-regulating, opposing way, forming the core of the self-protective strategy seen in grandiose narcissism. Placing this self-regulatory emotional dynamic at the center of grandiose narcissism, we present an affect-centric process model that aims to explain antagonistic self-protective behaviors shown by individuals high on grandiose narcissism. Specifically, we conceptualize these self-protective processes as rooted in a strong status motive, combined with a stable tendency to experience envy in response to upward comparisons that pose ego or status threats. To regulate envy, we propose that contempt is automatically activated, leading to devaluation through indifference, which in turn fosters social conflict. We further apply these dynamics to explain the change of relationship trajectories (short-term acquaintance vs. long-term acquaintance) of individuals high on grandiose narcissism, by suggesting the envy-contempt dynamic to exacerbate in long-term acquaintances, in which individuals high on grandiose narcissism tend to defend against the uprise of feelings of dependency on their partners admiration. While supporting empirical findings are outlined throughout the article, we finally propose a variety of questions that should be addressed in the future in order to scrutinize our model.